Retrospective analysis of adverse drug reaction reporting forms associated with penicillin family antibiotics (pcne-drp 9.0) based on drug-related approach - A. V. Matveev; A. E. Krasheninnikov; E. A. Egorova; E. I. Koniaeva (Фармация и фармакология (Пятигорск), 2020)
A widespread use of β-lactam antibiotics such as penicillins in practical medicine, and its authorized use in special categories of patients (e.g. children, pregnant and lactating women, the elderly) requires a critical investigation of their safety as well as the obligatory risk assessment before conducting antibacterial pharmacotherapy.The aim of the work was the conduction of a retrospective study of adverse reactions cases, the identification and analysis of drug-related problems (DRP) associated with the use of penicillin family antibiotics.Materials and methods. The objects of the study were adverse drug reactions (ADR) associated with the use of penicillin family antibiotics in inpatient and outpatient facilities, as well as the cases of self-treatment, which were recorded in the official ADR reports and then inputted in the regional (Republic of Crimea) database of spontaneous reports called ARCADe (Adverse Reactions in Crimea, Autonomic Database). The covered period is 2009–2018. The analysis of DRP was carried out using the 9.0 version of the qualification system DRP PCNE (Pharmaceutical Care Network Europe Foundation).Results. The data analysis of ADR reporting forms has revealed that Amoxicillin clavulanate and Amoxicillin were the most frequent cause of ADR. A high incidence of penicillins ADR in pediatric patients (from 0 to 18 years) – 142 cases – has been found. The clinical manifestations of reactions included drug hypersensitivity reactions (309 cases), dyspeptic disorders (28 cases) and disorders of the central nervous system (5 cases). The incidence of serious ADR was 113 cases (33% of the total number of ADR in the study), which indicates a rather high risk of developing severe ADR for penicillins, resulted in a significant decrease in the quality of patients’ lives.Conclusion. The detection of DRP using the PCNE V9.0 approach is a useful and promising tool important to improve the quality of pharmacotherapy and their adherence to treatment. The highest DRP values which were observed for Amoxicillin clavulanate and Amoxicillin, may indicate a high frequency of irrational use of these drugs.List of abbreviations: DRP – drug related problems; ADR – adverse drug reactions; INN – international non-patented name